Robert H. Gardiner and the reunification of worldwide Christianity in the Progressive Era - Woolverton, John Frederick, 1926-2014 (University of Missouri Press, 2005)
"Biography of Robert Hallowell Gardiner III, Progressive Era leader of the Christian ecumenical movement, the Young Manhood Movement, and the World Council of Churches. Includes discussions of George Wharton Pepper, Francis Stetson, John R. Mott, Newman Smyth, Cardinal James Gibbons, Bishop Charles Henry Brent, Vida D. Scudder, and others"--Provided by publisher.